Preko izkustva zla in etike skrbi do vzgoje in kateheze za mir - Vodičar, Janez (Bogoslovni vestnik, 2025)
The more we talk about peace, the less there is in the world. Therefore, there is an ever-increasing need for education that would change this. In this article, we examine possible ways of education and catechesis that could give more hope for peace in the future. We begin our analysis with a fundamental belief in good, because we assume that this is an essential prerequisite for a dignified education. At the same time, with the help of Paul Ricoeur's phenomenological analysis of fundamental myths about the origin of evil, we discover different ways in which humanity encounters evil. Through the theogonic myths, we finally arrive at the biblical Job, where we find a starting point for education for peace in a gratuitous relationship. In the Jewish tradition, human powerlessness grows into responsibility. We take educational principles from the ethics of care, which is based on the fundamental assumption of original human care — responsibility — and combine them with various mythical explanations for the origin of evil. The basic characteristics of such an education, based on dialog, attention to the needs of disciples and the building of a responsible community, are used as guidelines for a catechesis that should contribute to peace. Such catechesis responds to the demands of the Church's teaching and the Christian tradition of understanding the origin of evil.
Keywords: catechesis; education for peace; ethics of care; etika skrbi; kateheza; miti o zlu; myths about evil; Noddings, Nel; Ricour, Paul; vzgoja za mir